Hydrological dynamics of the Subaé River basin in the Recôncavo of Bahia (Research, Society and Development, 2021)
Properly monitor hydrological processes in a watershed despite being essential, sometimes turns relatively complex, Mainly because of scarcity of necessary data. In this sense, the present study aimed to generate hydrological models of the Subaé River Basin, Bahia, Brazil, in a GIS environment, employing the Curve Number (CN) method as the basis. For this purpose, images from the LandSat8 Satellite (30 m), ALOS Satellite's DEM from PALSAR sensor (12.5 m), soil vector file on the scale 1:250,000 from IBGE and rainfall data from INMET were used. The acquired data were processed in a GIS environment, Using the Bhattacharya supervised classifier, the r.watershed algorithm and the SCS-CN method. The results were maps of Land Use and Coverage, Surface Runoff and Surface Runoff Rate. From the results it was possible to infer that the sum of the natural characteristics, like Relief, Soil and Precipitation together with anthropic factors, among which stands out the disordered urban occupation, provide an increase in surface runoff that in addition to resulting in flooding in the urban perimeter contribute to elevate the risk for soil erosion and water degradation in the study area.